Designing an AI-Assisted Speech-Based Interactive System for Home-Based Sentence Practice for Children - Wiafe, Elizabeth; Rudzicz, Frank; Escobedo, Lizbeth (Anais da Conferência Latino-Americana de Interação Humano-Computador (CLIHC); 2026: Anais da XII Conferência Latino-Americana de Interação Humano-ComputadorDO - 10.5753/clihc.2026.21174, 2026)
Expressive sentence construction is foundational to children’s academic development, yet opportunities for structured practice and receiving feedback outside clinical environments remain limited. This work-in-progress paper presents an AI-assisted speech-based interactive prototype designed to support home-based sentence formulation through multimodal prompts and automated feedback. The system integrates visual stimuli, guided target words, local speech recognition, and structured grammar-aware analysis that evaluates sentence completeness, target word use, complexity level, and contextual relevance through a conjunctive decision rule to provide supportive, non-diagnostic feedback. We describe the system architecture and outline a proposed pilot study with children aged 6-12, complemented by expert input from speech-language pathologists, to evaluate feasibility, usability, and perceived educational value.